Trace analyzer for NS-2 - Salleh A.U.; Ishak Z.; Din N.Md.; Jamaludin M.Z. (2023)
Network simulator 2 (NS-2) is an open source discrete event simulation tool used for simulating Internet protocol (IP) networks. It was developed by UC Berkeley and widely used worldwide for network simulation purposes. The NS-2 software uses TCL as a front-end interpreter and C++ as the back end network simulation engine. Network simulation scripts in TCL are used to create the network scenarios and upon the completion of the simulation, trace files that capture events occurring in the network are produced. The trace files would capture information that could be used in performance study, e.g. the amount of packets transferred from source to destination, the delay in packets, packet loss etc. However, the trace file is just a block of ASCII data in a file and quite cumbersome to access using some form of post processing technique. In order to ease the process of extracting data for performance study, the NS-2 Trace Analyzer is proposed. This software is a tool for extracting and presenting trace files for the network simulation environment of NS-2. The NS-2 Trace Analyzer software consists of three layers. The first layer is the source layer which consists of the trace file data. The second layer is the processing layer. This layer processes the data obtain from the source and convert it to meaningful format for the third layer. The third layer is the presentation layer. This layer presents meaningful data in the form of graph, table and report for network performance study, i.e. throughput, end-to-end delay, packet loss and jitter. Through the NS-2 Trace Analyzer the user would be able to do performance study of a network scenario through interactive GUI. This will benefit the user since he or she can concentrate on developing new algorithms or new architectures rather spending too much time on post processing of data. 2006 IEEE.